Differential response of Zea mays L. in relation to weed control and different macronutrient combinations - Khan, M.A.; Kakar, S.; Marwat, K.B.; Khan, I.A. (Universiti Kebangsaan Malaysia, 2013)
Time of weed control and fertilizer application usually decide the profitability of crop production. The effects of weed control and macronutrients on maize crop were investigated. The study was undertaken in March 2009, using a RCBD design with split plot arrangements. The experimental set up was established at the Agricultural University Peshawar and seedbeds were prepared with the proper moisture regime. Maize was planted with one plot left weed free for first six weeks while another infested with weed. The combinations of macronutrients used were nitrogen, phosphorus, potassium, nitrogen-phosphorus, nitrogen-potassium, phosphorus-potassium and nitrogen-phosphorus-potassium. Control (no fertilizer) was included for comparison. The observations revealed that when a comparison was made between the application of fertilizers and weed control, the latter proved more important because weed infested plots had no harvestable maize plants. The role of main nutrients in crop production is well known and cannot be left aside, however weed infestation does not provide us a fair choice of fertilizers application. The maximum maize grain yield was recorded under nitrogen-phosphorus combination and promising results were obtained. The weeds and maize benefited equally in terms of fresh and dry weed biomass with an application of fertilizer in particular N singly or together with P. In view of this, application of fertilizer should be changed from broadcast to band and/or placement. In general, a positive interaction was seen between N and P promoting the growth of maize and weeds. It can be said that herbicide application for weed control is important because of the fact that hand weeding is not economical, difficult, time consuming because of perennial weeds and hot weather conditions in the month of June.